Reactor protection system conceptual design for Triga Puspati reactor using LabVIEW software - Manan, K.E.; Yakub, F.; Ab Rashid, Mohd Zamzuri; Ahmad, M.A.; Minhat, M.S. (2023)
This paper presents a conceptual design for replacing the current Reactor Protection System (RPS) to improve reactor safety and allow the potential implementation of a multi-purpose research reactor. The RPS is a part of the TRIGA PUSPATI Reactor (RTP), which has been operated since 1982. However, RTP must be strengthened for the device to be sustainable and satisfy the International Atomic Energy Agency's safety guidelines (IAEA). The RPS conceptual design is utilizing LabVIEW software throughout this research. The trip function can be designed for the RPS to regulate the armature electromagnetic system to control the rod's height level using the software. The software is also used to establish the interlock function, which controls the sequence and safety of the rod's movement. The design is then simulated to see observe the operation, safety and efficiency of RPS. The RPS in this research will be further combined with actual detectors like fission chambers, instrumented fuel components, thermocouples, and neutron measurement systems that exist in the RTP.